DIPLOMASI BUDAYA INDONESIA DALAM PENYELENGGARAAN ACARA “KERATON” DI SEATTLE TAHUN 2011-2024 - Shalsabila Desiani Ekaputri; Gracia Medyate Sinulingga; Reyhan Auni Fazari; Ario Bimo Utomo (Halu Oleo University, 2025)
This study aims to analyse the role of the Keraton event as a tool for Indonesian cultural diplomacy and its impact on Indonesia's relationship with the international community in Seattle. Using a descriptive method with a qualitative approach, this research gathers primary data through interviews and secondary data through literature reviews and social media analysis. The time frame of this study spans from 2011, the first year the Keraton event was held, to 2024, marking the most recent implementation of the event. The results show that the Keraton event has successfully become an effective platform for introducing various aspects of Indonesian culture, such as traditional food, dance, music, and batik, to the international community. In addition, the event has strengthened intercultural relations and reinforced Indonesia's positive image in the eyes of the world. This study also finds the importance of the active participation of the Indonesian community in Seattle in making this event a success as a form of citizen diplomacy. The implications of this research emphasise the significant role of cultural events in introducing national cultural identities abroad and strengthening international relations.